Regional mechanism for sustainable development - Vladyka M.; Averina S.; Tikunov D.; Serebrova T. (E3S Web of Conferences, 2023)
Technologization and resource consumption of modern regional production complexes actualizes the paradigm of their sustainable development. Ecosystem development of mesoterritoriums requires the use of integrated approaches, the creation of conditions and incentives. The concept of using an integrated mechanism to achieve sustainable development of the region as a technology for managing the territorial economy, focused on improving the efficiency of territorial production complexes, the implementation of priority areas in science, technology and critical technologies is put forward. The components of the management tools for the sustainable development of mesosystems are proposed, representing the internal structure and sequence of stages of interrelated directions of movement of the territorial economy to the desired state. This mechanism can be considered as a set of actions, the implementation of which will lead to socio-economic progress at a new level. A comprehensive regional mechanism of sustainable development is substantiated, which activates the process of economic and social changes in five directions: economic, spatial, social, digital and environmental, ensuring the implementation of the strategy of transformational processes. The proposed integrated regional mechanism of sustainable development can be applied at different levels of territorial management. In the conditions of modern realities of the implementation of the new regionalism, it is advisable to ensure stable trends in territorial development on the basis of platform and ecosystem approaches.